Digitalisasi Media Promosi UMKM melalui Perancangan Website Company Profile Kopi Azol - Endah Rahayu; Gina Nofa Lisa; Ressi Illahi; Zulfitri Yani; Sularno (Jurnal Imiah Pengabdian Pada Masyarakat (JIPM), 2026)
The rapid advancement of digital technology has fundamentally transformed business practices, creating both opportunities and challenges for Micro, Small, and Medium Enterprises (MSMEs). Kopi Azol, a local coffee shop MSME in Padang City, West Sumatra, demonstrated extraordinary resilience after surviving fire and flood disasters, yet lacked a formal digital presence in the form of an official website. This community service activity, conducted through the Project-Based Learning (PBL) framework of the Web Design course at Politeknik Negeri Padang, aimed to design and develop a professional company profile website for Kopi Azol. The method encompassed field observation, structured interviews, needs analysis, UI/UX-based website design using the SITE123 platform, implementation, and evaluation. The resulting website, accessible at http://6a1eb0ebb24f0.site123.me/, features seven key sections: Home, Video Profile, About, Menu, Services, Testimonials, and Contact, integrated with WhatsApp, Instagram, and Google Maps. The website strengthens Kopi Azol's digital branding, broadens its market reach, and enhances consumer trust. This initiative demonstrates that academic-community collaboration through PBL can produce measurable digital solutions for local MSMEs.